If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-12x + 30) + (-17x + -4) = 360 + -75 + -27 Reorder the terms: (30 + -12x) + (-17x + -4) = 360 + -75 + -27 Remove parenthesis around (30 + -12x) 30 + -12x + (-17x + -4) = 360 + -75 + -27 Reorder the terms: 30 + -12x + (-4 + -17x) = 360 + -75 + -27 Remove parenthesis around (-4 + -17x) 30 + -12x + -4 + -17x = 360 + -75 + -27 Reorder the terms: 30 + -4 + -12x + -17x = 360 + -75 + -27 Combine like terms: 30 + -4 = 26 26 + -12x + -17x = 360 + -75 + -27 Combine like terms: -12x + -17x = -29x 26 + -29x = 360 + -75 + -27 Combine like terms: 360 + -75 = 285 26 + -29x = 285 + -27 Combine like terms: 285 + -27 = 258 26 + -29x = 258 Solving 26 + -29x = 258 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + -29x = 258 + -26 Combine like terms: 26 + -26 = 0 0 + -29x = 258 + -26 -29x = 258 + -26 Combine like terms: 258 + -26 = 232 -29x = 232 Divide each side by '-29'. x = -8 Simplifying x = -8
| c^2+13c+42= | | 1/3x+3=-7/2x-3/2 | | 7-5(x-2)=47 | | 2+2(5)= | | 60(2)(1/2) | | 60(21/2) | | 1/3*-1/4 | | x^2+8xy-9y^2= | | 4x/4=10/4 | | -8+(-2)= | | 1/2x+1/3(-1/4y+10)=5 | | -3x+7x+(-2x)= | | 5x-3(-2x+4)=6 | | Log(x)=7.645 | | (4m-3)=15 | | ln(x)=7.645 | | [2p-3]=15 | | 46-2p=6-9p | | 5x+(-2x)+7= | | -6x-6(3x-2)=132 | | 46-2p=6-7p | | 2x-4/9=10 | | 31+x=0 | | (12x-4)+(14x-11)+(15x+5)=236 | | 6*12*9= | | -3(2x-4)=2(5-x) | | √5x-4=6 | | 4x-(x+2)=x-2 | | -9x+10=-4(x-3) | | 3x/5+1/4=7x/20-4 | | x-.9x=74 | | 3x+9=-2x+1 |